Nuevos Espacios Urbanos Para Nuevas Tendencias: Medicina Complementaria y Alternativa y Ciudades Medias Globales - Ramírez, Antonia; Martínez, Rosalía; Márquez, Miguel A. (European Scientific Journal, ESJ, 2017)
Complementary and alternative medicine refers to the use and benefit of non-allopathic medicines, which is presently increasing in Western societies. This study, on one hand, shows the presence and the form that this new fashion among the population adopts. On the other hand, it shows the spatial distribution of the tendency in CAM. This refers to its distribution according to neighborhoods and metropolitan territories. For this purpose, the city of Seville, Spain, a middle European city present in the network of global cities, has been selected for this study. To show this sociological reality, quantitative methodology has been conducted within two years beginning from 2013 to 2014. The database that was created provided information about the offer of the CAM, specifically 100 different practices related with the complementary and alternative medicine of 450 Centers and professionals. This is with a total of 1338 number of answers.